Pediatric Palliative Care in Africa: Towards its Universalization from the Perspective of Culture and Ethics (Revista Iberoamericana de Bioética, 2022)
In this paper we raise the need for the essential implementation of these programs in Africa. This should also take an approach that considers the continent's own cultural experience and in light of ethical principles adjusted to its reality.
Keywords: pediatric palliative; Africa; bioethics